Pengaruh Bauran Pemasaran Dan Efektifitas Strategi Pemasaran Terhadap Pengambilan Keputusan Konsumen Untuk Membeli Rumah Pada Developer “X” Di Madiun - Alfiah, Eka Nur; Syahrinullah, Syahrinullah (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
The purpose of this study is to determine the effect of the marketing mix on consumer decisions to buy houses at Developer "X" and to determine the effectiveness of marketing strategies on consumer decisions to buy houses at Developer "X". The type of research used is explanatory research. the data used is data obtained from the results of a questionnaire distributed by the company selling houses at Developer "X". The population of this research is all levels of Madiun society and those who are prospective customers from Developer "X" for the ongoing project "A". Based on the results of the analysis it can be concluded as follows: a) There is a positive and significant influence from the marketing mix on consumer decisions to buy a house at Developer "X", b) The marketing strategy implemented by Developer "X" is considered quite effective in attracting consumer decision interest to buy a house at Developer "X".